Manajemen Hubungan Masyarakat dalam Pembentukan Brand Image Sekolah di MTsN 2 Kota Kediri - Untung Khoiruddin; Shela Ameylia Syah Putri (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This research aims to explain public relations efforts and media in forming the school brand image at MTsN 2 Kediri City. This research uses a qualitative approach with a case study type of research. This research was conducted at MTsN 2 Kediri City. In the data collection process, observation, interviews and documentation techniques were used. Data analysis uses the Miles, Huberman, and Saldana interaction model which includes data condensation, data display, and conclusions. Data checking in this study used increased persistence and triangulation. The results of this research show that: (1) Public relations efforts in forming a school brand image are by using a structured management system starting from planning, organizing, implementing and evaluating. (2) the media used by public relations in forming the school's brand image include direct communication, social media, print media, as well as accommodating community aspirations which are well managed through SOPs for community complaint guidelines (DOMAS). Public relations emphasizes social media because it has a wide reach and is more effective and efficient.